Measuring External Shock and Domestic Response in LDCs: Completing Balassa's Decomposition Method. - FitzGerald, E (1997)
The standard method for measuring external shocks transmitted to small open economies from the world economy was originally developed by Balassa and subsequently refined by McCarthy for the World Bank and Helleiner for the UNCTAD. This paper critically evaluates its neglect of the consequences of non-marginal changes in the exogenous variables, and sets out a corrected methodology which takes into account the second-order effects and distinguishes domestic reaction from policy response. The improved method is applied in detail to a single country (Mexico) and also to a cross-section of twenty-four LDCs for the 1970s and 1980s; and is shown to generate considerably more information than the standard method from a similar data base.